2017
DOI: 10.1002/cphc.201700725
|View full text |Cite
|
Sign up to set email alerts
|

Water Dynamics and Proton‐Transport Mechanisms of Nafion 117/Phosphotungstic Acid Composite Membrane: A Molecular Dynamics Study

Abstract: The use of a Nafion/phosphotungstic acid composite membrane and the impact of varying concentration of heteropoly acid (HPA) on the well-known effective mechanisms of proton transport were investigated by using classical and quantum hopping molecular dynamics simulation. Our simulations demonstrated that the HPA particles have a favorable influence on the Grotthuss mechanism in proton transportation at low hydration levels. From radial distribution function examinations, it was found that HPA particles were so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The ion exchange capacity (IEC) of the membrane is closely related to the water uptake (WU) [27, 28] and proton conductivity ( σ ) of the PEMs. The IEC values of the prepared PEMs are measured and displayed in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…The ion exchange capacity (IEC) of the membrane is closely related to the water uptake (WU) [27, 28] and proton conductivity ( σ ) of the PEMs. The IEC values of the prepared PEMs are measured and displayed in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating inorganic fillers such as silica has been an effective approach to further enhance the polymeric membrane stability [165] . Thanganathan, et al .…”
Section: Applicationmentioning
confidence: 99%
“…[164] Incorporating inorganic fillers such as silica has been an effective approach to further enhance the polymeric membrane stability. [165] Thanganathan, et al fabricated a hybrid membrane using phosphosilicate (P 2 O 5 -SiO 2 ), PTA. As-prepared membrane exhibited high proton conductivity of 10 À 2 -10 À 1 S cm À 1 at 120 °C with significantly enhanced thermal stability upto 300 °C.…”
Section: Proton Conductivitymentioning
confidence: 99%
“…Thei on exchange capacity (IEC) of the membrane is closely related to the water uptake (WU) [27,28] and proton conductivity (s)ofthe PEMs.The IEC values of the prepared PEMs are measured and displayed in Table S2. It is shown that the Nafion-Bi 12 -3 %h ybrid membrane exhibited considerably higher IEC values (0.95 AE 0.02 mmol g À1 )t han that of the RN membrane (0.86 AE 0.01 mmol g À1 ).…”
Section: Iec Water Uptake and Swelling Ratio Of Hybrid Membranementioning
confidence: 99%